2002
DOI: 10.1002/1522-2632(200211)87:5/6<629::aid-iroh629>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The fatty acid compositions of both lipid classes, triglycerides (TG) and phospholipids (PL), of caviar from 34 specimens of wild caught and 12 farmed specimens were measured. The investigated caviar samples of wild caught sturgeon comprised Huso huso, Acipenser gueldenstaedti, Acipenser stellatus and Polyodon spathula of different origins and those of farmed sturgeon from Acipenser baeri, A. stellatus, and P. spathula. Oleic acid (18 : 1 n–9) was the dominant fatty acid in TG of all caviar samples. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…The fatty acids profile detected in our samples matched with the general pattern reported in literature for fatty acid composition of sturgeon eggs and caviar [7,10,12,13,[19][20][21]. Among the saturated fatty acids (SFA), palmitic acid (16:0) proved to be the most abundant in both eggs and caviar samples, regardless of the species considered, according to the results of several previous publications [7,9,10,12,22].…”
Section: Whitesupporting
confidence: 89%
See 2 more Smart Citations
“…The fatty acids profile detected in our samples matched with the general pattern reported in literature for fatty acid composition of sturgeon eggs and caviar [7,10,12,13,[19][20][21]. Among the saturated fatty acids (SFA), palmitic acid (16:0) proved to be the most abundant in both eggs and caviar samples, regardless of the species considered, according to the results of several previous publications [7,9,10,12,22].…”
Section: Whitesupporting
confidence: 89%
“…As well as for LA, the level of ARA in caviar depends on the feed source supplied to sturgeons. Although ARA is the second most predominant among the n6 PUFA, our results showed significantly lower amounts than what is described in literature for wild caviar [9,11,19,24]. This can be imputed to the fact that ARA is highly present inside the aquatic trophic chains, especially in some algae and in some crustaceans [25] that represent the natural diet sources of wild sturgeons.…”
Section: Whitecontrasting
confidence: 68%
See 1 more Smart Citation
“…It has been reported that in eggs, during gametogenesis, lipoprotein biosynthesis preferentially utilises saturated and monounsaturated fatty acid from adipose and muscle tissues to provide metabolic energy, while n-3 PUFA are incorporated into phospholipids fraction of vitellogen and transferred via the serum into the eggs [34].…”
Section: Proximate and Fatty Acid Composition Of Caviarmentioning
confidence: 99%
“…For instance, DNA testing, based on genetic interspecific divergences and variations, is a well-known technique used to verify the species source of the product to date [4][5][6], even if the presence of hybrid sturgeons could make it difficult to correctly attribute a caviar to a single species. Moreover, it has been demonstrated that the chemical composition of caviar can lead to discriminate, above all, between eggs obtained from farmed vs. wild sturgeons [7][8][9] or eggs coming from different species [10].…”
Section: Introductionmentioning
confidence: 99%